Exosome-Mediated Crosstalk Between Tumor and Tumor-Associated Macrophages - Chen, Qi; Li, Yuefeng; Gao, Wujiang; Chen, Lu; Xu, Wenlin; Zhu, Xiaolan (Frontiers in Molecular Biosciences, 2021)
Exosomes are nanosized vesicles, derived from the endolysosomal compartment of cells and can shuttle diverse biomolecules such as nucleic acids, proteins, lipids, amino acids, and metabolites, which can reflect their origin cells. Delivery of these cargoes to recipient cells enables exosomes to influence diverse cellular functions. As one of the most abundant immune cells in the tumor microenvironment, tumor-associated macrophages (TAMs) are educated by the tumor milieu, which is rich in cancer cells and stroma components, to exert functions such as the promotion of tumor growth, immunosuppression, angiogenesis, and cancer cell dissemination. Herein, we focus on exosomes-mediated intercellular communication between tumor cells and TAM in the tumor microenvironment, which may provide new targets for anti-tumor treatment. In this review, we highlight the most recent studies on the effect of tumor/macrophage‐derived exosomes on macrophage/tumor function in different cancer types.